Gilligan's island. The complete first season [videorecording (DVD)] - Backus, Jim; Schafer, Natalie, 1900-1991; Denver, Bob; Tina Louise, 1934-; Hale, Alan, 1918-1990 (Warner Home Video, 2012)
After a three-hour pleasure cruise, the SS Minnow is washed ashore on an uncharted South Pacific island, leaving behind what would become TV's most famous castaways. Episodes include the: Two on a Raft; Home Sweet Hut; Voodoo Something To Me; Goodnight Sweet Skipper; Wrongway Feldman; President Gilligan; and many more. This title has been repackaged.